If the sequence has a common difference of 4, this means that:
![f(n+1)-f(n)=4\text{ for every n}](https://img.qammunity.org/2023/formulas/mathematics/college/11a2929kwidzpshrwy87rfev31gu9bs34c.png)
We can use that to find f(2), f(3), etc...
![\begin{gathered} f(2)-f(1)=4 \\ \Rightarrow f(2)=4+f(1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8rhz22ylbdj5t676nc7wyx308on6qdsy4l.png)
Substitute f(1)=3:
![f(2)=4+3=7](https://img.qammunity.org/2023/formulas/mathematics/college/kpgq493q8q7sy4czs62o4thxpaoh6b1x07.png)
The next term will be given by:
![\begin{gathered} f(3)=4+f(2) \\ \Rightarrow \\ f(3)=4+7=11 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/37sc2glgl6lz9f4shgo59qowlfdvag75ez.png)
By adding 4 to the previous term, it follows that f(4)=15, f(5)=19, and so on.
The sequence 3, 7, 11, 15, 19 appears in the option C.